2006
DOI: 10.1007/s00268-005-0270-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Extrathyroid Extension of Papillary Thyroid Carcinoma: Massive but Not Minimal Extension Affects the Relapse‐free Survival

Abstract: These findings suggest that (1) upgrading of T category for tumors with massive extension is appropriate, whereas that for tumors with only minimal extension is not, and (2) careful surgical treatment and postoperative follow-up are required for tumors with massive extension to posterior organs other than the recurrent laryngeal nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
192
4
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(215 citation statements)
references
References 14 publications
15
192
4
4
Order By: Relevance
“…The presence of macroscopic, but not microscopic, lymph-node involvement is the strongest risk factor for LNR while a bilateral dissection of central and lateral compartments is associated with lower risk at multivariate analysis. As previously reported, extra-thyroidal invasion (1,5,6,(14)(15)(16) and male gender (1,5,6,15,17) are also related to an increased risk. The present data clearly show that the effects of LND differ in patients with and without macroscopic lymphnode metastases.…”
Section: Discussionsupporting
confidence: 63%
“…The presence of macroscopic, but not microscopic, lymph-node involvement is the strongest risk factor for LNR while a bilateral dissection of central and lateral compartments is associated with lower risk at multivariate analysis. As previously reported, extra-thyroidal invasion (1,5,6,(14)(15)(16) and male gender (1,5,6,15,17) are also related to an increased risk. The present data clearly show that the effects of LND differ in patients with and without macroscopic lymphnode metastases.…”
Section: Discussionsupporting
confidence: 63%
“…Male gender, multicentricity, and advanced age are known to be conventional prognostic factors of papillary carcinoma [3,4], but these features did not affect PMC progression during observation. Furthermore, we failed to establish a relationship between carcinoma enlargement and tumor size at diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…Usually, papillary carcinoma is indolent and grows slowly, although cases having certain biological characteristics, such as clinically apparent node metastasis in the lateral compartment (N1b in the International Union Against Cancer [UICC] tumor node metastasis [TNM] classification [1]) and massive extrathyroid extension (pT4 [1]) are progressive [2][3][4]. Papillary carcinoma measuring 1.0 cm or less is defined as papillary microcarcinoma (PMC) by the World Health Organisation (WHO) classification.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the prevalence of clinical thyroid papillary carcinoma was 1.9-11.7 per 100,000 people of all ages (22), suggesting that the subclinical thyroid carcinoma is almost one thousand times lower than the apparent clinical type. A previous study (23) even suggested that patients without high-risk factors of thyroid carcinoma should not immediately undergo surgery.…”
Section: Discussionmentioning
confidence: 87%